Russian Federation : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
In this study, the following are listed: GDP by sector and expenditure, gross industrial output by sector, employment by sector, industrial employment by sector, indicators of hidden unemployment, selected labor market indicators, unemployment rate by regions, consumer price inflation and CPI weights, industrial producer prices, wages, pensions and per capita income, federal government budget execution, regional and local government operations, extrabudgetary fund operations, monetary surveys, balance of payment projections, origin of imports, composition of merchandise imports, foreign currency disbursements to the federal government, and nonsovereign/sector financial account.